Analisis Profitabilitas, Likuiditas, dan Leverage terhadap Kinerja Manajemen: Emiten Consumer Non-cyclicals BEI Periode 2019-2023 - Eva Yanis Lafione; Wastam Wahyu Hidayat; Gilbert Rely (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The purpose of this study was to determine whether profitability, liquidity, and Leverage affect management performance. The population in this study was taken from consumer non-cyclicals issuers listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method and amounted to 90 samples. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co. Then using the Statistical Package for Sciene (SPSS) version 25 as a tool for analyzing. The hypothesis in this study was tested using descriptive statistical analysis, classical assumption test, multiple linear analysis test, and hypothesis testing. The conclusion of this study states that (1) profitability has no effect on management performance (2) liquidity has a positive effect on management performance (3) Leverage has a positive effect on management performance.